2012
DOI: 10.1088/0953-8984/24/22/225303
|View full text |Cite
|
Sign up to set email alerts
|

Back-to-back Schottky diodes: the generalization of the diode theory in analysis and extraction of electrical parameters of nanodevices

Abstract: We report on the analysis of nonlinear current-voltage characteristics exhibited by a set of blocking metal/SnO(2)/metal. Schottky barrier heights in both interfaces were independently extracted and their dependence on the metal work function was analyzed. The disorder-induced interface states effectively pinned the Fermi level at the SnO(2) surface, leading to the observed Schottky barriers. The model is useful for any two-terminal device which cannot be described by a conventional diode configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 33 publications
12
90
0
Order By: Relevance
“…4,24 We further note that the post DEP thermal anneal step helps to eliminate the presence of mid-gap states at the Au-CuO interface, which can otherwise lead to Fermi level pinning. 25 Second, we obtain a poor fit of our data with the operational form 26 of the back-toback Schottky diode (see characteristic fitting in supplementary material 27 S1 for IV obtained at 260 K). Finally, as we show next, a low voltage, linear IV is observed in all our data which is not characteristic of back-to-back Schottky conduction mechanism, either.…”
mentioning
confidence: 91%
“…4,24 We further note that the post DEP thermal anneal step helps to eliminate the presence of mid-gap states at the Au-CuO interface, which can otherwise lead to Fermi level pinning. 25 Second, we obtain a poor fit of our data with the operational form 26 of the back-toback Schottky diode (see characteristic fitting in supplementary material 27 S1 for IV obtained at 260 K). Finally, as we show next, a low voltage, linear IV is observed in all our data which is not characteristic of back-to-back Schottky conduction mechanism, either.…”
mentioning
confidence: 91%
“…This type of 2-terminal devices can be thought of as MSM devices202122. We have used such a device model to analyze the opto-electronic data on SNW photodetectors made from Cu:TCNQ NWs1423.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative model worth considering when dealing with contacts between metals and gapped material is that of Chiquito et al, which describes back-to-back Schottky diodes and has been reported to explain the I (V ) behavior of one-dimensional semiconducting SnO 2 nanobelts contacted by various metals [39]. In this case, the nonlinear effects observed are primarily due to the work function of the metal used to contact the semiconductor, which is a situation well described as a Schottky interface, at the two ends of a narrow strip of an otherwise ballistic conductor.…”
Section: Discussionmentioning
confidence: 99%